PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR TERCATAT DI BURSA EFEK INDONESIA - Miftakhul Fauziyah; Rokhmad Subagyo; Ummu Sholihah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This study aims to analyze the effect of profitability, leverage, and liquidity on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Firm value is proxied by Price to Book Value (PBV), while profitability is measured using Return on Assets (ROA), leverage using the Debt-to-Equity Ratio (DER), and liquidity using the Current Ratio (CR). This study uses a quantitative approach with a purposive sampling method, resulting in 90 observational data from the financial statements of manufacturing companies that meet the research criteria. The data analysis technique used is multiple linear regression, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that leverage has a significant effect on firm value, while profitability and liquidity do not. This finding indicates that investors consider a company's funding structure more than its profit-generating ability or liquidity level in assessing manufacturing companies during the study period. This research is expected to provide empirical contributions to company management in formulating financial policies and to investors in making investment decisions.